2011
DOI: 10.1007/s00464-011-2011-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of haptic feedback in laparoscopic surgery skill acquisition

Abstract: Background The benefits of haptic feedback in laparoscopic surgery training simulators is a topic of debate in the literature. It is hypothesized that novice surgeons may not benefit from the haptic information, especially during the initial phase of learning a new task. Therefore, providing haptic feedback to novice trainees in the early stage of training may be distracting and detrimental to learning. Objective A controlled experiment was conducted to examine the effect of haptic feedback on the learning c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 25 publications
(22 reference statements)
0
53
0
Order By: Relevance
“…The compliance of an object is an estimate of its elasticity (Bergmann Tiest & Kappers, 2009). Zhou et al (2012) discovered that the reduced tactile feedback experienced in laparoscopic surgery reduces the surgeon's ability to discriminate the compliance of tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The compliance of an object is an estimate of its elasticity (Bergmann Tiest & Kappers, 2009). Zhou et al (2012) discovered that the reduced tactile feedback experienced in laparoscopic surgery reduces the surgeon's ability to discriminate the compliance of tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, combined hapticvisual training modes have an advantage over either haptic or visual modes alone for tasks that have a force component, such as surgical simulation [15]. However, limitations to surgical training with a haptic feedback simulator were reported in one study; even though haptic feedback enabled a significant improvement in a laparoscopic suturing and knot-tying task with a higher learning rate, the surgeons reached a plateau after 5 h of training with the haptic device [16]. Recent work by Olsson et al reported an immersive virtual environment setup with a colocated visuohaptic display and head-tracking capabilities [17].…”
Section: Discussionmentioning
confidence: 99%
“…This hesitation was caused, at least partially, by technical reasons: in early surgical robotic systems, haptic feedback was either patched on or estimated/simulated, the performance of which was rather limited, hence surgeons were less in favor of the outcomes [48]. However, with the fast developments in robotic technology, recent surgical systems with haptic feedback are equipped with new force sensors and very well implemented control [52,53], and as a result, more and more studies showed that haptic feedback became one of the most wanted features for the next generation of surgical robots [54][55][56][57][58][59].…”
Section: Innovations For Hapticsmentioning
confidence: 99%